The public intellectual : between philosophy and politics - Melzer, Arthur M.; Weinberger, J.; Zinman, M. Richard (Rowman & Littlefield, 2003)
The editors bring together a wide variety of noted scholars to discuss the characteristics, nature, and role of public thinkers. By looking at scholarly life in the West, this work explores the relationship between thought and action, ideas and events, reason and history.